A systematic review of mindset interventions in mathematics classrooms: What works and what does not? - Bui Phuong; Pongsakdi Nonmanut; McMullen Jake; Lehtinen Erno; Hannula-Sormunen Minna M. (Elsevier, 2025)
A growing body of research has suggested that mindset is one powerful predictor of students' academic achievement and that students are likely to hold self-beliefs about the malleability or stability of their academic abilities. In the domain of mathematics education, a belief in ‘math brain’ – as something you do or do not possess – is widely prevalent. Studies have shown that teachers and students are more likely to consider achievement in mathematics than achievement in other academic domains to be due to inborn ability. Most growth mindset-related research in schools is domain-general; however, given the prevalence of strong beliefs about the innateness of mathematical ability, possible idiosyncratic effects of mindset interventions in the mathematics domain may have been overlooked by research reviews and meta-analyses that do not examine domain-specific effects. The purpose of this paper is to compile and synthesise quantitative and qualitative research on interventions in mathematics classrooms that aim to change or foster teachers' and/or students' beliefs/mindset in primary and secondary schools and the reported impacts of these interventions (16 studies). The interventions in these studies were identified and sorted based on their targets (teacher-focused or student-focused), content (implicit theories of intelligence (ITI) intervention for general domains or in mathematics domain), and delivery mode (technology-based or in-contact). The results suggested most of the considered studies were quantitative and used student-focused interventions. Moreover, when ITI interventions were conducted specifically in the mathematics domain, positive results were reported, regardless of the intervention target or content or mode of delivery, whereas general ITI interventions yielded mixed results. Future studies should therefore consider the impacts of domain-specific effects and intervention targets when designing mindset interventions.​​​​​​